Tissue-specific expression and activity of cytochrome P450 1A and 3A in rainbow trout (Oncorhynchus mykiss) - Burkina, Viktoriia; Zamaratskaia, Galia; Sakalli, Sidika; Giang, Pham Thai; Zlabek, Vladimir; Rasmussen, Martin Krøyer (Toxicology letters, 2021)
Piscine cytochrome P450 (CYP) enzymes play an important role in the metabolism of xenobiotics. Xenobiotics often act as inducers of CYP1A1 and CYP3A expression and activity in fish. We compared constitutive mRNA expression of CYP1A1, CYP3A27, and CYP3A45 and catalytic activity of CYP1A (7-ethoxyresorufin-O-deethylation, EROD) and CYP3A-like (benzyloxy-4-trifluoromethylcoumarin-O-debenzyloxylation, BFCOD) enzymes in the following six rainbow trout tissues: liver, gill, heart, brain, intestine, and gonad. mRNA expression and activity were present in all investigated tissues. The CYP1A1 mRNA expression was higher in the liver, gill, heart, and brain compared to gonad and intestine. The intestine was the main site of CYP3A27 and CYP3A45 expression. The highest EROD and BFCOD activity was observed in liver tissue followed in descending order by heart, brain, gill, intestine, and gonad. Such differences might be related to the role of CYP physiological functions in the specific tissue. Rainbow trout exposure to 50 mg/kg of β-naphthoflavone for 48 h resulted in a 7.5- and 5.9-fold increase in liver EROD and BFCOD activity, respectively. In vitro EROD activity inhibition with ellipticine showed tissue-specific inhibition, while ketoconazole decreased BFCOD activity by 50-98 % in all tissues. Further studies are needed to identify all CYP isoforms that are responsible for these activities and modes of regulation.
Keywords: Liver; Animals; CYP3A; Cytochrome P-450 CYP3A; Gene Expression Regulation, Enzymologic; Intestines; Female; Gills; regulace genové exprese enzymů; játra; ženské pohlaví; cytochrom P-450 CYP3A; žábry; messenger RNA; mozek; Cytochrome P-450 CYP1A1; Sex Characteristics; RNA, Messenger; střeva; P450; Male; CYP inhibitors; Brain; pohlavní dimorfismus; cytochrom P-450 CYP1A1; CYP1A1; Oncorhynchus mykiss; zvířata; mužské pohlaví; Myocardium; myokard; Catalytic activity